Characteristics and immune-enhancing activity of pectic polysaccharides from sweet cherry (Prunus avium). (15th July 2018) - Cao, Jinping; Tang, Dandan; Wang, Yue; Li, Xian; Hong, Li; Sun, Chongde
Highlights: Two chief water soluble polysaccharides (PAPS-1 and PAPS-2) from sweet cherry were purified. PAPS-1 and PAPS-2 were deduced as type I rhamnogalacturonan pectic polysaccharides. PAPS-1 and PAPS-2 significantly induced the activation of RAW264.7 cells. Abstract: Two water soluble polysaccharides components PAPS-1 and PAPS-2 with homogeneously distributed molecular weight were obtained from Prunus avium . PAPS-1 and PAPS-2 contained GalA: Ara: Gal: Rha: GluA: Glu in 49.38: 32.39: 10.68: 4.66: 1.94: 0.48 and 77.18: 14.91: 3.39: 3.46: 0.93: 0.19 M ratios respectively, as well as trace amount of mannose and fucose. Infrared spectroscopy (IR), nuclear magnetic resonance (NMR) and methylation analysis indicated that both fractions were type I rhamnogalacturonan (RG-I) pectic polysaccharides with glycan side chains constituted mainly of arabinose with minor amount of galactose. Galacturonic acid methylation and sugar acetylation was found in both PAPS-1 and PAPS-2. Both PAPS-1 and PAPS-2 significantly induced the NO release from RAW264.7 cells and the expression of several immune-related molecular (TNFα, IL6, IL10, GCSF, iNOS, COX-2) was induced in RAW264.7 cells.